Hall effect in printed Nanoparticulate Silicon Networks - Gonfa, Girma Goro (Department of Physics, 2014)
Silicon nanoparticles for the application of printed electronics were successfully synthesised and characterised. High energy milling has been proven to yield uncontaminated powder of median particle size 150 nm satisfying a lognormal distribution. Single crystalline P- and N-type silicon wafers, and metallurgical grade silicon were used as starting materials. The structural characterisation of all milled powders using X-ray diffraction (XRD), Small Angle X-ray Scattering (SAXS) and electron diffraction proved that the silicon nanoparticles are polycrystalline with a crystallite size of about 40 nm. For the first time, we have formulated printable semiconducting inks from nanoparticulate silicon. Silicon nanoparticles were mixed with organic binders, such as linseed oil and acrylic, to produce printable inks. Similarly nanoparticulate silicon ink, doped with inorganic salts, which is a different procedure to conventional impurity doping of the silicon structure, was produced with linseed oil. A home-built Hall measurement system was used to characterise layers of doped ink, for which a complete carrier type reversal was observed. Based on the result of elemental mapping, two possible models were suggested to explain the doping effect. A state-of-the-art Hall measurement system was used to perform field dependent analysis of screen printed silicon inks in van der Pauw geometry. A magnetoconductivity tensor model was developed to extract the carrier properties. All the layers were demonstrated to have at least two carrier types. Inks produced from P-type silicon maintained their carrier type, but reversal was observed for the N-type layers. The mobility of the carriers is better or comparable to similar classes of semiconducting materials. 2 More information on the interparticle connections were obtained from IV and impedance spectroscopy measurements which demonstrated the capacitive effects present in the printed layers. The capacitors originate at the interfaces between the metal and the layers and between the particles.